The Bahamas : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report, 2005)
This Selected Issues paper for The Bahamas reports that the largest portion of tourism expenditure in The Bahamas comes from stayover visitors, and total tourism spending has been stagnant. The Bahamas is a small open economy highly dependent on tourism and the offshore financial sector. Private consumption expenditure in the country or countries of origin is the most important determinant of tourism in The Bahamas.